Optimization on radiation dose and image quality in paediatric computed tomography examination - Muhammad, Nor Azura (2021)
Computed tomography (CT) scan examinations have been acknowledged for its high dose exposure contribution. This is troublesome for paediatric as they are susceptibility to radiation and receives higher probability of radiation - induced cancer risk. Lowering the radiation dose while maintaining patient diagnostic value is a vital feature of all dose management practices. Henceforth, the first phase of this study is to establish the local Diagnostic Reference Levels (DRLs) for paediatric CT examination with consideration of the noise index. This retrospective study was approved by Medical Research Ethics Committee (MREC) of University of Malaya Medical Center (approval no: MREC id no 2018920-6690). One thousand one hundred and ninety-two (1192) paediatric patients underwent CT brain, CT thorax and CT chest-abdomen-pelvis (CAP) examinations were recorded. For each group, data such as scanning acquisition parameters and dose information, volume weighted CT dose index (CTDIvol), dose-length product (DLP) and the effective dose (E) were evaluated. The CT dose values between all age groups have differed significantly with p-value = 0.0001. There was a significant variation in doses and noise intensity among children of different ages. The second phase of this study involves adoption of ICRP Publication 103 report and Biological Effects of Ionizing Radiation (BEIR) VII report to determine the radiation-induced cancer risk among subjects. Notably, the highest incidence lifetime attributable risk (LAR) of liver cancer is found in the age group (10-15) with 5.9 out of 100,000 and 2.5 out of 100,000 respectively. The highest cancer risk was in the liver based on the ICRP 103 recommendations for both genders in age group of (1 - < 5) were 3.6 and 1.5 per 100,000 procedures in male and female respectively. The final phase of this study observed the impact of dose in radiosensitive organ and its influence towards image quality in CT Chest-Abdomen-Pelvis (CAP) examination after applying CT optimization process. The organ doses were evaluated by using a 1-year-old anthropomorphic phantom with a thermoluminescence dosimeter (TLD) as a passive dosimeter. In a whole, nine CT protocols were applied for optimization process and the image quality was evaluated by determine the signal to noise ratio (SNR) and contrast to noise ratio (CNR) of phantom images. Notably, the optimization process indicates a potential reduction in a dose up to 20 % to 50 % along with reducing tube voltage, tube current and with increasing slice collimation without compromising the diagnostic value. By turning off the Automatic Tube Current Modulation (ATCM) feature increases the radiation absorbed dose by 80%. Hence, regular CT dose monitoring and optimization procedures will reduce the probability of radiation-induced cancer risk and provide safer imaging practices.